2015
DOI: 10.1186/s12955-015-0302-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating functional outcomes in adolescents with attention-deficit/hyperactivity disorder: development and initial testing of a self-report instrument

Abstract: BackgroundEngaging adolescents in decisions about their health may enhance their compliance with treatment and result in better health outcomes. Treatment outcomes in attention-deficit/hyperactivity disorder (ADHD) are rarely evaluated from the adolescents’ point of view. There is also concern that adolescents with ADHD may not have insight about the impacts of their disease. This article describes research conducted to understand the experiences of adolescents with ADHD and how the research was used to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Participants were referred by clinicians in the San Juan metropolitan area. Individual semistructured interviews (n=40) 3 focus groups (n=20) were conducted with a different cohort of participants (ie, not those who had been previously interviewed) Top 10 concepts for good QoL: 1) to feel able to accomplish goals; 2) to have a good attitude towards others; 3) to get good grades; 4) to respect others/not offend others; 5) to pay attention/concentrate at school; 6) to do things/participate in activities with others; 7) to behave well with others/not be rude; 8) to avoid looking for or getting in trouble; 9) to be healthy/to have good physical health; and 10) to not do things in a rush/to do them slowly Socialization=most prevalent focus group theme Being able to practice sports was most important for good QoL in interviews Believed not having a mental health condition would improve QoL N/A Dewey et al 15 To investigate HRQoL and peer relationships in adolescents with DCD and ADHD 44 adolescents in Canada (aged 11–18) recruited from a cohort study examining genetics and neurobiology of motor and attention problems ADHD only: n=9 DCD only: n=9 ADHD+DCD: n=10 Normally developing: n=19 Semistructured interviews exploring various aspects of HRQoL Most participants in ADHD-only group reported only enjoying nonsedentary activities (eg, playing sports, dancing, swimming) Close friends were a good source of support for all participants ADHD participants reported feeling alone, lonely, ignored, left out, or marginalized (as compared with typically developing peers) N/A Hareendran et al 16 To describe the experience of living with ADHD from the perspective of adolescents and their caregivers, for use in the creation of a new self-report instrument 3 teachers who had worked with students with ADHD 60 adolescents (aged 13–17) with a clinician- confirmed diagnosis of ADHD No other Axis I or II conditions (per DSM-IV) Stable off medication for 1 week (if stimulant)–4 weeks (if nonstimulant) or on medication for at least 4 weeks 60 primary caregivers (age 18+) of an adolescent with ADHD Individual interviews with teachers Individual interviews with adolescents Individual interviews with caregivers Interviews with adolescents and caregivers together (questions were addressed to adolescents first, then to caregivers to provide additional detail) Difficulties wit...…”
Section: Resultsmentioning
confidence: 99%
“…Participants were referred by clinicians in the San Juan metropolitan area. Individual semistructured interviews (n=40) 3 focus groups (n=20) were conducted with a different cohort of participants (ie, not those who had been previously interviewed) Top 10 concepts for good QoL: 1) to feel able to accomplish goals; 2) to have a good attitude towards others; 3) to get good grades; 4) to respect others/not offend others; 5) to pay attention/concentrate at school; 6) to do things/participate in activities with others; 7) to behave well with others/not be rude; 8) to avoid looking for or getting in trouble; 9) to be healthy/to have good physical health; and 10) to not do things in a rush/to do them slowly Socialization=most prevalent focus group theme Being able to practice sports was most important for good QoL in interviews Believed not having a mental health condition would improve QoL N/A Dewey et al 15 To investigate HRQoL and peer relationships in adolescents with DCD and ADHD 44 adolescents in Canada (aged 11–18) recruited from a cohort study examining genetics and neurobiology of motor and attention problems ADHD only: n=9 DCD only: n=9 ADHD+DCD: n=10 Normally developing: n=19 Semistructured interviews exploring various aspects of HRQoL Most participants in ADHD-only group reported only enjoying nonsedentary activities (eg, playing sports, dancing, swimming) Close friends were a good source of support for all participants ADHD participants reported feeling alone, lonely, ignored, left out, or marginalized (as compared with typically developing peers) N/A Hareendran et al 16 To describe the experience of living with ADHD from the perspective of adolescents and their caregivers, for use in the creation of a new self-report instrument 3 teachers who had worked with students with ADHD 60 adolescents (aged 13–17) with a clinician- confirmed diagnosis of ADHD No other Axis I or II conditions (per DSM-IV) Stable off medication for 1 week (if stimulant)–4 weeks (if nonstimulant) or on medication for at least 4 weeks 60 primary caregivers (age 18+) of an adolescent with ADHD Individual interviews with teachers Individual interviews with adolescents Individual interviews with caregivers Interviews with adolescents and caregivers together (questions were addressed to adolescents first, then to caregivers to provide additional detail) Difficulties wit...…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly affected areas, according to both the patients and their caretakers, are the physical and psychosocial (emotional, social and school) domains of QoL. 19 Hareendran et al 4 found that adolescents with ADHD reported significant functional impairments associated with their condition, especially with regard to school, home, leisure activities and social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…2 ADHD is characterized by symptoms of inattention, hyperactivity and impulsivity, with onset before age 12, which often continue into adolescence and adulthood, in one of three forms of clinical presentation: combined, predominantly inattentive, and predominantly hyperactive/impulsive (APA, 2013). According to expert opinion 3 and patients themselves 4 the most common functional impairments in ADHD are associated with neuropsychological performance (especially attention) 3 school performance and social functioning. 3,4 The presence of neuropsychological impairments in patients with ADHD relative to control subjects is corroborated by studies involving neuropsychological assessment, especially of the executive functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to expert opinion 3 and patients themselves 4 the most common functional impairments in ADHD are associated with neuropsychological performance (especially attention) 3 school performance and social functioning. 3,4 The presence of neuropsychological impairments in patients with ADHD relative to control subjects is corroborated by studies involving neuropsychological assessment, especially of the executive functions. [5][6][7] However, short-term memory is the only cognitive function to have shown a specific association with the severity of hyperactivity symptoms.…”
Section: Introductionmentioning
confidence: 99%